Increasing cisplatin exposure promotes small-cell lung cancer transformation after a shift from glucose metabolism to fatty acid metabolism - Qiu-yu Zhao; Wen-jun Liu; Jian-guang Wang; He Li; Jia-lu Lv; Yumeng Wang; Chun Wang (Journal of Cancer Research and Clinical Oncology)
Abstract Objectives Lung cancer is a leading cause of global cancer mortality. Clinical observations reveal that histological transformation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) is accompanied by mutations in TP53 and RB1. By applying gradually increasing cisplatin concentrations to mimic the escalating drug pressure within the tumor microenvironment, this study investigated the link between phenotypic transformation to SCLC in cisplatin-resistant human lung adenocarcinoma cells and alterations in cellular energy production pathways. Materials and Methods We established two cisplatin-resistant NSCLC cell lines with varying resistance levels. RNAseq analyses identified TP53 and RB1 gene mutations. Comprehensive functional assays were performed to characterize A549/DDP1 μg/mL and A549/DDP3 μg/mL cells, focusing on proliferation and migratory capabilities. Cellular bioenergetics were assessed through glycolysis and oxidative phosphorylation analyses. Western blotting was employed to examine epithelial-mesenchymal transition (EMT), glucose metabolism, and lipid metabolism markers. Cell cycle distribution was analyzed by flow cytometry. Additionally, a xenograft mouse model was developed for in vivo validation. Results TP53 and RB1 mutations were associated with cisplatin concentration-dependent phenotypic transformation, with A549/DDP cells acquiring a more aggressive SCLC-like phenotype (In the article we call the A549/DDPSCLC cells). Analysis of cell bioenergetics profiling and Western blot analyses revealed enhanced glucose metabolism in A549/DDP1 μg/mL cells, while A549/DDPSCLC cells exhibited predominant lipid metabolism. Compound3K and Etomoxir specifically inhibit the activity of PKM2 and CPT1A, respectively, with Etomoxir demonstrating substantially inhibited A549/DDPSCLC cells growth and more cell cycle arrest in the G0/G1 phase. Combinatorial of Compound3K and Etomoxir effectively induced cell death in A549/DDPSCLC phenotype cells in vitro. Etomoxir alone or combined with Compound3K significantly inhibited tumor growth in vivo, with enhanced efficacy in the combination group. Conclusions This study provides the first evidence of cisplatin concentration-dependent metabolic reprogramming during NSCLC-to-SCLC transformation. We identified a phenotypic transition from NSCLC to SCLC accompanied by a metabolic shift from glucose to fatty acid metabolism, offering new insights into therapeutic strategies for treatmentresistant lung cancer.